Storage temperature dictates the ability of chicken embryos to successfully resume development by regulating expression of blastulation and gastrulation genes - Pokhrel, Narayan; Genin, Olga; Sela-Donenfeld, Dalit; Cinnamon, Yuval (Frontiers in Physiology, 2022)
Abstract The avian embryo has a remarkable ability that allows it to suspend its development during blastulation for a long time at low temperatures, and to resume normal development when incubated. This ability is used by poultry hatcheries to store eggs prior to incubation. We have previously found that this ability correlates with the temperature during storage; embryos recover much better following prolonged storage at 12oC rather than at 18oC. However, the molecular and cellular mechanisms underlying these differences are poorly understood. To successfully resume development following storage, the embryo has to shift from the blastulation phase to gastrulation. Several genes are known to partake in the blastulation-to-gastrulation transition under normal conditions, such as the pluripotency-related genes Inhibitor of DNA Binding 2 (ID2) and NANOG that are expressed during blastulation, and the gastrulation-regulating genes NODAL and Brachyury (TBXT). However, their expression and activity following storage is unknown. To elucidate the molecular mechanisms that initiate the ability to successfully transit from blastulation to gastrulation following storage, embryos were stored for 28 days at 12oC or 18oC, and were assessed either prior to incubation, 12, or 18 hours of incubation at 37.8oC. Immediately following storage at 18oC group showed remarkable impaired morphology compared to the blastoderm of the 12oC group and of non-stored control embryos. Concurrently with these, expression of ID2 and NANOG was maintained following storage at 12oC similar to the control group, but was significantly reduced upon storage at 18oC. Nevertheless, when the 18oC-stored embryos were incubated, the morphology and the reduced genes were reverted to resemble those of the 12oC group. At variance, key gastrulation genes, NODAL and its downstream effector Brachyury (TBXT), which were similarly expressed in the control and the 12oC group, were not restored in the 18oC embryos following incubation. Notably, ectopic administration of Activin rescued NODAL and TBXT expression in the 18 oC group, indicating that these embryos maintain the potential to initiate. Collectively, this study suggests a temperature-dependent mechanisms that direct the transition from blastulation to gastrulation. These mechanisms promote a successful developmental resumption following prolonged storage at low temperatures.